Marketing training strategies that pharmaceutical sales managers use to reduce unethical behavior - Aseel Bin Sawad; Kate Andrews (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Some pharmaceutical company sales representatives are using bribes to encourage increasing medication prescriptions. In 2012, GlaxoSmithKline paid $3 billion on a felony charge related to bribing doctors to prescribe the company's medications. Using Hunt and Vitell's general theory of marketing ethics, the purpose of this qualitative multiple case study was to explore strategies some sales managers in the pharmaceutical industry used to improve marketing training to reduce unethical sales representative behavior. MATERIALS AND METHODS: Data were collected from company reports and documents provided by sales managers and semistructured interviews with five sales managers of different pharmaceutical companies in the northeast region of the United States. Data were analyzed using thematic analysis and Yin's 5-step process of compiling, disassembling, reassembling, interpreting, and concluding thematic data analysis. RESULTS: Three themes emerged from data analysis: developing ethical standards, developing organizational policy, and implementing training and development programs. A key recommendation is that pharmaceutical sales managers identify ethical standards to inculcate in their business practices to achieve ethical marketing training that can result in sales representatives' ethical behavior. The implications for positive social change include the potential for sales managers to develop strategies to reduce unethical behavior in the pharmaceutical industry. CONCLUSION: Reducing unethical behavior may lead to more trust between patients and physicians, improving patient satisfaction and promoting prosperity for the community through enhancing the quality of health care.